Analisis Perbandingan Pendapatan Petani Pola Tanam Monokultur Dan Polikultur Di Kecamatan Meureudu Kabupaten Pidie Jaya - Rizael Zoelfahmie; Safrida Safrida; Sofyan Sofyan (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
In the District Meureudu, there are two types of cropping farming in paddy fields, namely Monoculture cropping pattern and cropping patterns poly. Monoculture is planting only one crop a year, namely rice, whereas polyculture cropping is planting more than one plant within a year, namely rice and soybeans. The method used in this research is survey method. The sampling technique is cluster sampling and data used are primary data and secondary data. Average - Average area of land that did monoculture is 0.22 hectares, while the area of land on the cropping pattern polyculture is 0.15. Average - Average harvests of farmers practicing monoculture of 3.2 ton / year, while the average - average yields in cropping patterns polyculture 1.9 ton / year for rice and 0.48 Kg / year for soybeans. Comparison of farmers using monoculture and polyculture in District Meureudu is 65: 35. In general, farmers in Sub Meureudu that uses monoculture earn 42 million / ha / year, while the use of polyculture cropping patterns to earn 58 million / ha / Year. Constraints faced by farmers practicing monoculture of the interview that the pest rodents, sparrows and waterways, while the polyculture cropping patterns from the interviews that the pest rodents, sparrows, waterways and livestock citizens. Keywords: Income, monoculture, and poly